Tree Species Shape Soil Bacterial Community Structure and Function in Temperate Deciduous Forests - Dukunde, Amélie; Schneider, Dominik; Schmidt, Marcus; Veldkamp, Edzo; Daniel, Rolf (Frontiers in Microbiology, 2019)
Amplicon-based analysis of 16S rRNA genes and transcripts was used to assess the effect of tree species composition on soil bacterial community structure and function in a temperate deciduous forest. Samples were collected from mono and mixed stands of Fagus sylvatica (beech), Carpinus betulus (hornbeam), Tilia sp. (lime), and Quercus sp. (oak) in spring, summer and autumn. Soil bacterial community exhibited similar taxonomic composition at total (DNA-based) and potentially active community (RNA-based) level, with fewer taxa present at active community level. Members of Rhizobiales dominated at both total and active bacterial community level, followed by members of Acidobacteriales, Solibacterales, Rhodospirillales, and Xanthomonadales. Bacterial communities at total and active community level showed a significant positive correlation with tree species identity (mono stands), and to a lesser extent with tree species richness (mixed stands). Approximately 58 and 64 % of indicator operational taxonomic units (OTUs) showed significant association with only one mono stand at total and active community level, respectively, indicating a strong impact of tree species on soil bacterial community composition. Soil C/N ratio, pH, and P content similarly exhibited a significant positive correlation with soil bacterial communities, which was attributed to direct and indirect effects of forest stands. Seasonality was the strongest driver of predicted metabolic functions related to C fixation and degradation, and N metabolism. Carbon and nitrogen metabolic processes were significantly abundant in spring, while C degradation gene abundances increased from summer to autumn, corresponding to increased litterfall and decomposition. The results revealed that in a spatially homogenous forest soil, tree species diversity, and richness are dominant drivers of structure and composition in soil bacterial communities.